Bronchial Thermoplasty Global Registry (BTGR): 2-year results - Torrego, Alfons; Herth, Felix J; Munoz-Fernandez, Ana M; Puente, Luis; Facciolongo, Nicola; Bicknell, Stephen; Novali, Mauro; Gasparini, Stefano; Bonifazi, Martina; Dheda, Keertan; Andreo, Felipe; Votruba, Praha; et al. (BMJ open, 2021)
ObjectivesBronchial thermoplasty (BT) is a device-based treatment for subjects ≥18 years with severe asthma not well controlled with inhaled corticosteroids and long-acting beta-agonists. The Bronchial Thermoplasty Global Registry (BTGR) collected real-world data on subjects undergoing this procedure.DesignThe BTGR is an all-comer, prospective, open-label, multicentre study enrolling adult subjects indicated for and treated with BT.SettingEighteen centres in Spain, Italy, Germany, the UK, the Netherlands, the Czech Republic, South Africa and AustraliaParticipantsOne hundred fifty-seven subjects aged 18 years and older who were scheduled to undergo BT treatment for asthma. Subjects diagnosed with other medical conditions which, in the investigator’s opinion, made them inappropriate for BT treatment were excluded.Primary and secondary outcome measuresBaseline characteristics collected included demographics, Asthma Quality of Life Questionnaire (AQLQ), Asthma Control Test (ACT), medication usage, forced expiratory volume in one second and forced vital capacity, medical history, comorbidities and 12-month baseline recall data (severe exacerbations (SE) and healthcare utilisation). SE incidence and healthcare utilisation were summarised at 1 and 2 years post-BT.ResultsSubjects’ baseline characteristics were representative of persons with severe asthma. A comparison of the proportion of subjects experiencing events during the 12 months prior to BT to the 2-year follow-up showed a reduction in SE (90.3% vs 56.1%, p<0.0001), emergency room visits (53.8% vs 25.5%, p<0.0001) and hospitalisations (42.9% vs 23.5 %, p=0.0019). Reductions in asthma maintenance medication dosage were also observed. AQLQ and ACT scores improved from 3.26 and 11.18 at baseline to 4.39 and 15.54 at 2 years, respectively (p<0.0001 for both AQLQ and ACT).ConclusionsThe BTGR demonstrates sustained improvement in clinical outcomes and reduction in asthma medication usage 2 years after BT in a real-world population. This is consistent with results from other BT randomised controlled trials and registries and further supports improvement in asthma control after BT.Trial registration numberNCT02104856.